FIRST DETRITAL ZIRCON GEOCHRONOLOGY DATA FOR CLASTIC ROCKS OF THE EAST SAKHALIN ACCRETIONARY TERRANE - I. A. Alexandrov; V. V. Ivin; A. I. Malinovsky; S. Yu. Budnitskiy (Геодинамика и тектонофизика, 2022)
First detrital zircon geochronology data and results of geochemical studies for clastic rocks of the Rymnik and Nabil zones of the East Sakhalin accretionary terrane, located within the region of the East Sakhalin Mountains, are presented. The studies have been carried out at the Center for Collective Use of Far Eastern Geological Institute of the Far East Branch of the Russian Academy of Sciences in Vladivostok. The established geochemical features suggest that the source of the clastic material of the zones was felsic rocks of the deeply eroded continental island arc or arcs. Although the geochemical characteristics are similar, there are sharp differences between the detrital zircons’ age distribution patterns of rocks of these zones. In the sandstone of the Nabil zone, 75 % of the zircon grains are of the middle Cretaceous age (94–108 Ma) with a peak of 96 Ma, 15 % are the middle Permian-Early Jurassic, and 10 % are the Precambrian (mainly Paleoproterozoic). The sandstone of the Rymnik zone has a more complex (polymodal) pattern of the detrital zircon age distribution, with a significant contribution of the Precambrian grains (37 %). Most of the grains belong to the Early Jurassic (peak 196 Ma) and the Early Cretaceous (peak 137 Ma), with 47 % of the Mesozoic grains. The likely provenances of the clastic material were the Middle Cretaceous volcanic arcs of the Asian eastern margin older complexes of the continent.